How to be a quantitative ecologist : the 'A to R' of green mathematics and statistics - Matthiopoulos, Jason (Hoboken, NJ : Wiley, 2011)
"Ecological research is becoming increasingly quantitative, yet students often opt out of courses in mathematics and statistics, unwittingly limiting their ability to carry out research in the future. This textbook provides a practical introduction to quantitative ecology for students and practitioners who have realised that they need this opportunity. The text is addressed to readers who haven't used mathematics since school, who were perhaps more confused than enlightened by their undergraduate lectures in statistics and who have never used a computer for much more than word processing and data entry. From this starting point, it slowly but surely instils an understanding of mathematics, statistics and programming, sufficient for initiating research in ecology. The book's practical value is enhanced by extensive use of biological examples and the computer language R for graphics, programming and data analysis. Provides a complete introduction to mathematics statistics and computing for ecologists. Presents a wealth of ecological examples demonstrating the applied relevance of abstract mathematical concepts, showing how a little technique can go a long way in answering interesting ecological questions. Covers elementary topics, including the rules of algebra, logarithms, geometry, calculus, descriptive statistics, probability, hypothesis testing and linear regression. Explores more advanced topics including fractals, non-linear dynamical systems, likelihood and Bayesian estimation, generalised linear, mixed and additive models, and multivariate statistics. R boxes provide step-by-step recipes for implementing the graphical and numerical techniques outlined in each section. How to be a Quantitative Ecologist provides a comprehensive introduction to mathematics, statistics and computing and is the ideal textbook for late undergraduate and postgraduate courses in environmental biology. "With a book like this, there is no excuse for people to be afraid of maths, and to be ignorant of what it can do." Professor Tim Benton, Faculty of Biological Sciences, University of Leeds, UK"--
"The book will comprise two equal parts on mathematics and statistics with emphasis on quantitative skills"--
Machine generated contents note: 0. How to start a meaningful relationship with your computer Introduction to R -- 0.1 What is R? -- 0.2 Why use R for this book? -- 0.3 Computing with a scientific package like R -- 0.4 Installing and interacting with R -- 0.5 Style conventions -- 0.6 Valuable R accessories -- 0.7 Getting help -- 0.8 Basic R usage -- 0.9 Importing data from a spreadsheet -- 0.10 Storing data in data frames -- 0.11 Exporting data from R -- 0.12 Further reading -- 0.13 References -- 1. How to make mathematical statements Numbers, equations and functions 1.1 Quantitative and qualitative scales? Habitat classifications -- 1.2 Numbers? Observations of spatial abundance -- 1.3 Symbols? Population size and carrying capacity -- 1.4 Logical operations -- 1.5 Algebraic operations? Size matters in garter snakes -- 1.6 Manipulating numbers -- 1.7 Manipulating units -- 1.8 Manipulating expressions? Energy acquisition in voles -- 1.9 Polynomials? The law of mass action in epidemiology -- 1.10 Equations -- 1.11 First order polynomial equations? Linking population size to population composition -- 1.12 Proportionality and scaling? Simple mark-recapture? Converting density to population size -- 1.13 Second and higher-order polynomial equations? Estimating the number of infected animals from the rate of infection -- 1.14 Systems of polynomial equations? Deriving population structure from data on population size -- 1.15 Inequalities? Minimum energetic requirements in voles -- 1.16 Coordinate systems? Non-cartesian map projections -- 1.17 Complex numbers -- 1.18 Relations and functions? Food webs? Mating systems in animals -- 1.19 The graph of a function? Two aspects of vole energetics -- 1.20 First order polynomial functions? Population stability in a time series? Population stability and population change? Visualising goodness-of-fit -- 1.21 Higher-order polynomial functions -- 1.22 The relationship between equations and functions? Extent of an epidemic when the transmission rate exceeds a critical value -- 1.23 Other useful functions? Modelling saturation -- 1.24 Inverse functions -- 1.25 Functions of more than one variables -- 1.26 Further reading -- 1.27 References -- 2. How to describe regular shapes and patterns Geometry and trigonometry -- 2.1 Primitive elements -- 2.2 Axioms of Euclidean geometry? Suicidal lemmings, parsimony, evidence and proof -- 2.3 Propositions? Radio-tracking of terrestrial animals -- 2.4 Distance between two points? Spatial autocorrelation in ecological variables -- 2.5 Areas and volumes? Hexagonal territories -- 2.6 Measuring angles? The bearing of a moving animal -- 2.7 The trigonometric circle? The position of a seed following dispersal -- 2.8 Trigonometric functions -- 2.9 Polar coordinates? Random walks -- 2.10 Graphs of trigonometric functions -- 2.11 Trigonometric identities? A two-step random walk -- 2.12 Inverses of trigonometric functions? Displacement during a random walk -- 2.13 Trigonometric equations? VHF tracking for terrestrial animals -- 2.14 Modifying the basic trigonometric graphs? Nocturnal flowering in dry climates -- 2.15 Superimposing trigonometric functions? More realistic model of nocturnal flowering in dry climates -- 2.16 Spectral analysis? Dominant frequencies in Norwegian lemming populations? Spectral analysis of oceanographic covariates -- 2.17 Fractal geometry? Availability of coastal habitat? Fractal dimension of the Koch curve -- 2.18 Further reading -- 2.19 References -- 3. How to change things, one step at a time Sequences, difference equations and logarithms -- 3.1 Sequences? Reproductive output in social wasps? Unrestricted population growth -- 3.2 Difference equations? More realistic models of population growth -- 3.3 Higher-order difference equations? Delay-difference equations in a biennial herb -- 3.4 Initial conditions and parameters -- 3.5 Solutions of a difference equation -- 3.6 Equilibrium solutions? Unrestricted population growth with harvesting? Visualising the equilibria -- 3.7 Stable and unstable equilibria? Parameter sensitivity and ineffective fishing quotas? Stable and unstable equilibria in a density-dependent population -- 3.8 Investigating stability? Cobweb plot for unconstrained, harvested population? Conditions for stability under unrestricted growth -- 3.9 Chaos? Deterministic chaos in a model with density-dependence -- 3.10 Exponential function? Modelling bacterial loads in continuous time? A negative blue tit? Using exponential functions to constrain models -- 3.11 Logarithmic function? Log-transforming population time series -- 3.12 Logarithmic equations -- 3.13 Further reading -- 3.14 References -- 4. How to change things, continuously Derivatives and their applications -- 4.1 Average rate of change? Seasonal tree growth -- 4.2 Instantaneous rate of change -- 4.3 Limits? Pheromone concentration around termite mounds -- 4.4 The derivative of a function? Plotting change in tree biomass? Linear tree growth -- 4.5 Differentiating polynomials? Spatial gradients -- 4.6 Differentiating other functions? Consumption rates of specialist predators -- 4.7 The chain rule? Diurnal rate of change in the attendance of insect pollinators -- 4.8 Higher-order derivatives? Spatial gradients and foraging in beaked whales -- 4.9 Derivatives for functions of many variables? The slope of the sea floor -- 4.10 Optimisation? Maximum rate of disease transmission? The marginal value theorem -- 4.11 Local stability for difference equations? Unconstrained population growth? Density dependence and proportional harvesting -- 4.12 Series expansions -- 4.13 Further reading -- 4.14 References -- 5. How to work with accumulated change Integrals and their applications -- 5.1 Antiderivatives? Invasion fronts? Diving in seals -- 5.2 Indefinite integrals? Allometry -- 5.3 Three analytical methods of integration? Stopping invasion fronts -- 5.4 Summation? Metapopulations -- 5.5 Area under a curve? Swimming speed in seals -- 5.6 Definite integrals? Swimming speed in seals.
Includes bibliographical references and index.
Print version record.
Keywords: Ecology -- Mathematics; Ecology -- Vocational guidance; Ecology -- Research; Quantitative analysts; Quantitative research; Mathematics -- Vocational guidance; Ecology -- Mathematics; Ecology -- Research; Ecology -- Vocational guidance; Mathematics -- Vocational guidance; Science; Natural history; MATHEMATICS -- Probability & Statistics -- General; NATURE -- Ecology; NATURE -- Ecosystems & Habitats -- Wilderness; SCIENCE -- Environmental Science; SCIENCE -- Life Sciences -- Ecology; Ecology -- Mathematics; Ecology -- Research; Ecology -- Vocational guidance; Mathematics -- Vocational guidance; Quantitative analysts; Quantitative research; Electronic books